1983
DOI: 10.1016/0378-3782(83)90028-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of human adipose tissue during early gestation

Abstract: 805 normal-for-age human embryos and fetuses were used to study early prenatal fat development. The investigation included observations on stages of fat morphogenesis at the light microscopic level and computerized image analyses of fat lobule size and number. The buccal fat pad was selected as a model system for the analyses. Fat tissue differentiates between the 14th and the 16th weeks: there are five morphogenic phases in adipose tissue formation, strongly associated with the formation of blood vessels. Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
112
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 4 publications
7
112
0
5
Order By: Relevance
“…Interestingly, while in rodents WAT cannot be macroscopically detected during embryogenesis and develops mainly after birth, in human fetuses the formation of WAT starts well before birth (18). In accordance with the study of Poissonnet et al (19), we detected preadipocytes in periorbital tissue at 12 weeks of gestation using the preadipocyte marker Pref1, an epidermal growth factor-like domain-containing transmembrane protein expressed by adipocyte precursors and known to inhibit adipocyte differentiation (20,21). Our data indicated that during the early phases of fetal development PRKAR2B is the only PKA regulatory subunit expressed in human adipose tissue where it co-localizes with Pref1.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, while in rodents WAT cannot be macroscopically detected during embryogenesis and develops mainly after birth, in human fetuses the formation of WAT starts well before birth (18). In accordance with the study of Poissonnet et al (19), we detected preadipocytes in periorbital tissue at 12 weeks of gestation using the preadipocyte marker Pref1, an epidermal growth factor-like domain-containing transmembrane protein expressed by adipocyte precursors and known to inhibit adipocyte differentiation (20,21). Our data indicated that during the early phases of fetal development PRKAR2B is the only PKA regulatory subunit expressed in human adipose tissue where it co-localizes with Pref1.…”
Section: Discussionsupporting
confidence: 77%
“…Immature adipose tissue first appears in the fetus between 14 and 16 weeks of gestation. The stages in adipose development are as follows: i) emergence of undifferentiated loose connective tissue clusters, ii) mesenchymal condensation associated with angiogenesis, iii) differentiation of mesenchymal cells into preadipocytes within a vascular matrix, iv) emergence of primitive fat lobules characterized by the appearance of fat vacuoles appearing in the cytoplasm of the mesenchymal cells, and v) appearance of definitive fat lobules: fat lobules well separated from each other by dense septae of perilobular mesenchymal tissue (Poissonnet et al 1983). In terms of location, adipose tissue becomes first noticeable in the fetus at the head and neck, followed by the trunk, and finally in the upper and lower limbs (Poissonnet et al 1984).…”
Section: Adipose Tissue Biologymentioning
confidence: 99%
“…Chez l'Homme, les futurs obèses présentent dès la prime enfance une augmentation de ces deux paramètres plus rapidement que les individus normopondéraux et le phénomène persiste tout au long de la vie adulte [2]. Le développement du tissu adipeux, caractérisé par la formation d'adipocytes, se produit à partir de cellules précurseurs (préadipocytes) au cours du troisième trimestre de la grossesse puis après la naissance [3] mais reste possible à tout âge, des préadipocytes étant retrouvés dans le tissu adipeux souscutané chez les octogénaires des deux sexes [4]. Contrairement aux adipocytes, les cellules précurseurs peuvent se diviser.…”
Section: Développement Du Tissu Adipeux Et Lipides Alimentaires : Aspunclassified